ELEMEN PERANCANGAN KOTA YANG BERPENGARUH TERHADAP KUALITAS RUANG KOTA PADA JALAN JENDRAL SUDIRMAN KOTA SALATIGA - Risdian, Happy; Sari, Suzanna Ratih; Rukayah, Raden Siti (architecture department, Engineering faculty, Universitas Diponegoro, 2020)
Jalan Jendral Sudirman in Salatiga City is the part of Central Business District in Salatiga City. City planning elements according to Shirvani (1985) are land use, building form and mass, circulation and parking, open space, pedestrian ways , activity support, signage, and preservation. The existence element of urban design contained in Jalan Jendaral Sudirman will influence the quality of urban space. To determine this effect, this study uses a rationalistic qualitative method. Data collection method by means of literature study, field observations, interviews. Analysis method by analyze interview results. The results of this study indicate urban design elements influence to urban place quality.